2013
DOI: 10.1186/1756-0500-6-244
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with neck, shoulder and low back pains among medical students in a Malaysian Medical College

Abstract: BackgroundThe main purpose of the study was to assess the prevalence, body distributions and factors associated with musculoskeletal pain (MSP) among medical students in a private Malaysian medical college.MethodThis cross-sectional study was conducted among 232 medical students in a private medical college using an online questionnaire. The questionnaire was a modified Standardized Nordic Questionnaire focused on neck, shoulder and low back pain in the past week and the past year.ResultsTwo hundred and thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
102
9
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 21 publications
20
102
9
4
Order By: Relevance
“…This prevalence rate is in general agreement with the prevalence rates reported in the literature for college students which vary between 32.9% and 89.3% [6][7][8][9][10][11][13][14][15][16]18,19 . It is however higher than the 32.9% 8 and 36.9% 9 reported among nursing students in Japan, and lower than the 73.3% 18 and 80.0% 19 reported among nursing students in Korea and Australia respectively, as well as the reported prevalence among nurses at the workplace (i.e 78-84.4%) [30][31][32][33] .…”
Section: African Health Sciences Vol 15 Issue 2 June 2015supporting
confidence: 90%
See 3 more Smart Citations
“…This prevalence rate is in general agreement with the prevalence rates reported in the literature for college students which vary between 32.9% and 89.3% [6][7][8][9][10][11][13][14][15][16]18,19 . It is however higher than the 32.9% 8 and 36.9% 9 reported among nursing students in Japan, and lower than the 73.3% 18 and 80.0% 19 reported among nursing students in Korea and Australia respectively, as well as the reported prevalence among nurses at the workplace (i.e 78-84.4%) [30][31][32][33] .…”
Section: African Health Sciences Vol 15 Issue 2 June 2015supporting
confidence: 90%
“…The point prevalence of MSDs in the current study is higher than the 21.5% reported among nursing students in Japan 8 . It is however comparable to the estimated 46.9% 15 and 45.7% 16 prevalence rates among medical students in China and Malaysia respectively. There is a paucity of epidemiological studies that have explored the period-prevalence, point-prevalence and functional impairment of MSDs as triadic entities in college students.…”
Section: African Health Sciences Vol 15 Issue 2 June 2015supporting
confidence: 66%
See 2 more Smart Citations
“…The PSS questionnaire is widely employed, has strong normative Previous studies have reported a high incidence of musculoskeletal pain in medical students. A study at a Malaysian medical college found that 65% of students had musculoskeletal pain within the past year and reported an association with clinical years, computer use and a prior history of trauma [11]. A study at an Austrian medical school reported a prevalence of 53% for low back pain among medical students [12].…”
Section: Surveymentioning
confidence: 99%